Sintesis dan karakterisasi material mesopori MCM-41 menggunakan TMAOH dan garam anorganik K2SO4 - Soenandar Milian Tompunu Tengker; Iip Izul Falah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The MCM-41 synthesis has been performed starting from the dissolution stage of cetyltrimethylammonium bromide (CTAB) as a pore mold, then added tetramethylammonium hydroxide (TMAOH) and sodium sulfate salt (K2SO4) to improve the stability of the material. The crystallization process is carried out by adding sodium silicate and sodium aluminate dripwise into the solution. Decrease in pH of the solution was done by adding sulfuric acid (H2SO4 50%). The hydrothermal process is then carried out at 90°C for 36 hours, then washed, dried and calcined at 540°C. MCM-41 synthesis results were characterized using XRD, FTIR and TEM. The results showed that MCM-41 was successfully synthesized with a high degree of crystallography with 48Å lattice parameter size and had a uniform hexagonal pore structure.